2014
DOI: 10.1002/lary.24842
|View full text |Cite
|
Sign up to set email alerts
|

Microdebrider complications in laryngologic and airway surgery

Abstract: 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…However, since the microdebrider is a powered instrument that is frequently used in such confined spaces, usage can result in patient harm with user error or device malfunction. Several studies have identified complications of microdebrider use within the head and neck, but conclusions have largely been derived from single institutional data and focused on a single head and neck subsite 8–10 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, since the microdebrider is a powered instrument that is frequently used in such confined spaces, usage can result in patient harm with user error or device malfunction. Several studies have identified complications of microdebrider use within the head and neck, but conclusions have largely been derived from single institutional data and focused on a single head and neck subsite 8–10 …”
Section: Figurementioning
confidence: 99%
“…Several studies have identified complications of microdebrider use within the head and neck, but conclusions have largely been derived from single institutional data and focused on a single head and neck subsite. [8][9][10] Our study utilized the US Food and Drug Administration's (FDA) Manufacturer and User Facility Device Experience (MAUDE) Database to report the incidence and type of complications that occur with microdebrider usage in otolaryngologic surgeries. The MAUDE Database is an online resource that compiles the adverse events of medical devices.…”
mentioning
confidence: 99%
“…Much has been published about risks and complications related to sinus surgery, especially given the proximity of the paranasal sinuses to the orbit and brain 3–9 . However, complications specifically related to microdebrider use have been much less commonly explored, and to our knowledge, there are no research articles characterizing patterns of microdebrider device malfunction 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] However, complications specifically related to microdebrider use have been much less commonly explored, and to our knowledge, there are no research articles characterizing patterns of microdebrider device malfunction. [10][11][12][13] In 2014, the US Food and Drug Administration (FDA) launched openFDA, an open-source database that provides access to publicly available medical device reports, enforcement reports, and drug event reports (https://open.fda.gov/about/).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation